The Correlation Between Light Intensity, Age, And Working Period With Eye Fatigue In Computer Users - Raden Ayu Tanzila; Dinda Arista (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background: In the 21st century, many jobs involve using computers, estimated at around 75%, and there are 90 million adults who use computers daily. The use of technology often results in harmful effects, mainly if it is not appropriately managed. Factors affecting eye fatigue are work equipment, work environment (light intensity), work design, work duration, individual characteristics (age), or refraction.Objective: This study aims to determine the correlation between light intensity, age, and work duration with eye fatigue complaints in computer users at PT Bank X Palembang.Methods: This research is analytically observational. The population was all computer users at PT Bank X Palembang. Sampling was conducted in 40 samples that met the inclusion and exclusion criteria. Data were obtained by questionnaires and measuring lux meters. Data were analyzed bivariate using the chi-square test.Results: showed that 24 respondents (60%) worked with poor light Intensity and 27 respondents (67.5%) complained of eye fatigue. Based on statistical tests, there was a significant correlation between light Intensity (p = 0.027), there was no significant correlation between age (p = 1.000) and years of services (p = 1.000), and complaints of eye fatigue in user's computers at PT Bank X Palembang.Conclusion: poor light intensity can cause eye fatigue in computer users.